The Challenges of Permanence and Success in EJA-EPT at IFG in the Context of Emergency Remote Education (London Journal of Research In Humanities and Social Sciences, 2024)
This chapter aims to analyse the challenges of permanence and success faced by students in Youth and Adult Education integrated with Vocational Education at the Federal Institute of Goiás in the context of the Covid-19 pandemic, when the Emergency Education System was adopted due to social isolation. Methodologically, the study is qualitative and quantitative, and the data analysed is part of a survey carried out by the Observatory of the Brazilian Welfare State in partnership with the IFG’s Observatory of the World of Work, using information gathered from EJA-EPT students at the Federal Institute of Goiás. The study profiled the EJA student population at the institution, pointing out that this population has been severely impacted by the effects of the Covid-19 pandemic. The institutional effort was important in terms of guaranteeing the conditions of permanence during the term of the SEE, with even higher rates compared to the period immediately before the health crisis. However, although success rates, understood as approval, were considered high, the study pointed out that the objective conditions of the teaching and learning process did not satisfactorily fulfil the conditions for acquiring the knowledge provided for in the course curricula
Keywords: morality.; will; greed; Dependence; freedom; necessity; fate; fatalism; moral goodnefreedom; moral goodness; choice.ss; choice.; Psychosocial Risks; Operational Distress; Employees; Public and Private Organisations; politics; ideology; Religion; theology; social activity; Church.; COVID19; Permanence and success; SEE; EJA-EPT; Emergency Remote Education